A novel benzopyran-based colorimetric and near-infrared fluorescent sensor for Hg2+ and its imaging in living cell and zebrafish. (January 2020) - Lv, Hehong; Yuan, Gang; Zhang, Ganbing; Ren, Ziqi; He, Hanping; Sun, Qi; Zhang, Xiuhua; Wang, Shengfu
Abstract: A new near-infrared fluorescent probe (OTA-DCM), which contained a conjugated dicyanomethylene-benzopyran structure as the near-infrared fluorophore and dithia-dioxa-monoaza crown ether moiety as the receptor, was developed as a "naked-eye" indicator for Hg 2+ with rapid response, good binding constant (1.05 × 10 4  M −1 ), high selectivity and sensitivity. Moreover, OTA-DCM was successfully employed in real aqueous samples and fluorescent imaging for detection of Hg 2+ in living cells and zebrafish larvae with low cytotoxicity. Highlights: A new near-infrared fluorescent probe (OTA-DCM) was developed as a "naked-eye" indicator for Hg 2+ . The probe detected Hg 2+ with rapid response, good binding constant (1.05 × 10 4  M −1 ), high selectivity and sensitivity. The probe was employed in real aqueous samples and fluorescent imaging for detection of Hg 2+ in living cells and zebrafish larvae with low cytotoxicity.